2004
DOI: 10.1038/sj.emboj.7600225
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xL sequesters its C-terminal membrane anchor in soluble, cytosolic homodimers

Abstract: Bcl-x(L) is a potent inhibitor of apoptosis. While Bcl-x(L) can be bound to mitochondria, a substantial fraction, depending on the cell type or tissue, is found in the cytosol of healthy cells. Gel filtration and crosslinking experiments reveal that, unlike monomeric Bax, Bcl-x(L) migrates in a complex of approximately 50 kDa in the cytosol. Co-immunoprecipitation experiments indicate that Bcl-x(L) in the cytosol forms homodimers. The C-terminal hydrophobic tails of two Bcl-x(L) molecules are involved in homod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
145
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(162 citation statements)
references
References 35 publications
15
145
1
1
Order By: Relevance
“…3 Moreover, a Raf-1-binding site within the BH4 domain of BCL-2 might integrate pathways of resistance towards apoptosis with other cellular-signaling events. [18][19][20] It was therefore tempting to speculate that overexpression of BCL-x L might result in a translocation of BCL-x L to intracellular structures other than the mitochondria, for example the cytoskeleton or the inner cell membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Moreover, a Raf-1-binding site within the BH4 domain of BCL-2 might integrate pathways of resistance towards apoptosis with other cellular-signaling events. [18][19][20] It was therefore tempting to speculate that overexpression of BCL-x L might result in a translocation of BCL-x L to intracellular structures other than the mitochondria, for example the cytoskeleton or the inner cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, a substantial fraction of antiapoptotic BCL-x L has been found in a 50 kDa cytosolic homodimer complex in nontumor cells exogenously expressing BCL-x L , addressing the question of additional cytosolic effects. 3 Other BCL-2 family proteins locate physiologically to intracellular membranes. 4 BCL-2 family proteins have mainly been studied as positive or negative regulators of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Oleinick's group had found that Bcl-x L was as sensitive as Bcl-2 to photodamage in adhering cells [14]. This difference was eventually traced to a unique property of many suspension cell cultures, i.e., localization of Bcl-x L in the cytosol [15]. Fractionation studies revealed that this was also true for the mouse leukemia L1210 cell line, but not for adhering MCF-10A cells (Fig.…”
Section: Apoptotic Responses To Pdt: the Role Of Bcl-2mentioning
confidence: 95%
“…Jeong et al [50] demonstrated that these dimers involved the binding of the C-terminal α helix of one protein to the hydrophobic groove of the second one. Since the Bax structure is very similar to that of Bcl-xl under native conditions, Jeong et al [50] reported a possible hetero-dimerisation between Bax and Bcl-xl involving the replacement of Bax Hα9 by Bcl-xl CT in the hydrophobic cleft. Yet, this interaction was only seen in the presence of detergents or with a C-truncated form of Bax, suggesting that a first modification in the structure of Bax is necessary to unlock the protein.…”
Section: Bax Binding To the Proteinsmentioning
confidence: 99%